Seals and sealing handbook - Flitney, Robert (Elsevier/Butterworth-Heinemann, 2007)
Wherever machinery operates there will be seals of some kind ensuring that the machine remains lubricated, the fluid being pumped does not leak, or the gas does not enter the atmosphere. Seals are ubiquitous, in industry, the home, transport and many other places. This 5th edition of a long-established title covers all types of seal by application: static, rotary, reciprocating etc. The book bears little resemblance to its predecessors, and Robert Flitney has re-planned and re-written every aspect of the subject. No engineer, designer or manufacturer of seals can afford to be without this unique resource. *Wide engineering market *Bang up to date! *Only one near competitor, now outdated.